2018
DOI: 10.1007/s11250-018-1764-7
|View full text |Cite
|
Sign up to set email alerts
|

Sanitary measures in piggeries, awareness, and risk factors of African swine fever in Benue State, Nigeria

Abstract: The present study describes assessment of sanitary measures in piggeries of Benue State, Nigeria, to identify the risk factors of African swine fever. Questionnaires were distributed to 74 respondents consisting of piggery owners and attendants in different piggeries across 12 local government areas (LGAs) to collect data for this study. Sanitary measures in piggeries were observed to be generally very poor, though respondents admitted being aware of ASF. Piggeries located within 1-km radius of a slaughter sla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 15 publications
1
8
0
1
Order By: Relevance
“…The slaughter slabs were particularly highlighted as high-risk points for disease introduction and transmission. Other workers have confirmed the major role of the slaughter slabs in the introduction and transmission of ASF [34][35][36]. In the current work, firstly, pigs arrived at the slaughter slabs routinely and, if unsold, were kept for a few days, closely interacting with other pigs, and were then returned to the originating farms.…”
Section: Discussionsupporting
confidence: 67%
“…The slaughter slabs were particularly highlighted as high-risk points for disease introduction and transmission. Other workers have confirmed the major role of the slaughter slabs in the introduction and transmission of ASF [34][35][36]. In the current work, firstly, pigs arrived at the slaughter slabs routinely and, if unsold, were kept for a few days, closely interacting with other pigs, and were then returned to the originating farms.…”
Section: Discussionsupporting
confidence: 67%
“…As shown in Figure 3A-3B, the pig numbers of susceptibility, incidence and death in rural areas exceed that of in suburban areas. This can partly be explained that most of commercial pig farms are mainly located in the urban suburbs, they can effectively control the ASF epidemics together with higher level biosecurity and various management measures [12,13]. Meanwhile, the majority of backyard pig farms with either a low or very low biosecurity level are scattered, correspondingly, the management measures of various norms are relatively primitive resulting in a delayed response to the epidemic, which increases the pig numbers of susceptibility, incidence and death.…”
Section: Characteristics Of Asf Epidemic In Suburban and Rural Areasmentioning
confidence: 99%
“…The presence of wild suids , soft ticks of the Ornithodoros moubaba complex, and poor biosecurity measures have long been known as risk factors for ASF [8, 14]. Recent studies in Kenya and Nigeria have identified the following as risk factors for ASF: the presence of a slaughter slab within 1-km radius to the piggery, presence of refuse dump sites within 1-km radius to piggery, wearing of piggery unit protective clothing outside the piggery premises, external sourcing of replacement stock, the dry season, feed sources, and tick control [4, 10].…”
Section: Discussionmentioning
confidence: 99%
“…Clinically, ASF manifests in peracute and acute forms, although subacute and chronic forms may also occur [1, 4–6]. In spite of efforts to develop vaccines to control the disease, success has been elusive [7, 8].…”
Section: Introductionmentioning
confidence: 99%